1963
DOI: 10.1099/00221287-33-3-401
|View full text |Cite
|
Sign up to set email alerts
|

The Cultivation of Some Rumen Oligotrich Protozoa

Abstract: SUMMARYThe rumen oligotrich protozoa, Eremoplastron bovis (Dogiel, 1927), E. brevispinurn (Kofoid & MacLennan, 1932), Entodifiium longifiucleatum (Dogiel, 1925), E. ovimum (Dogiel, 1927), Eudiplodinium nzaggii (Fiorentini, 1889) and various Epidinium species have been cultured in mixed culture for over 7 months. The medium consisted of rice starch, dried grass and casein in a mineral salt solution +rumen liquor. No antibiotics were used.Preliminary studies showed that sodium sulphide causes inhibition of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1964
1964
1982
1982

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…In contrast those working elsewhere (i.e. Coleman, I 960; Clarke, 1963) have been unable to obtain good protozoal growth in the absence of either of these materials. Jarvis & Hungate (1968) also found that soluble materials such as bovine serum and a protozoal extract increased the protozoal growth rate for a few days, whereas in the experiments described above with Entodinium simpZex and previously with E. caudatum (Coleman, 1960) particulate matter (e.g.…”
Section: Cultivation Of Entodinium Simplex 89 Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast those working elsewhere (i.e. Coleman, I 960; Clarke, 1963) have been unable to obtain good protozoal growth in the absence of either of these materials. Jarvis & Hungate (1968) also found that soluble materials such as bovine serum and a protozoal extract increased the protozoal growth rate for a few days, whereas in the experiments described above with Entodinium simpZex and previously with E. caudatum (Coleman, 1960) particulate matter (e.g.…”
Section: Cultivation Of Entodinium Simplex 89 Discussionmentioning
confidence: 70%
“…Gutierrez & Davis (1962) cultivated Epidinium ecaudatum in vitro for 5 months but obtained populations of only 12oo/ml. Clarke (1963) maintained Eremoplastron bovis in unspecified numbers for 5 months and mixed entodiniomorphs for somewhat longer, while Mah (1964) maintained up to 1000 Ophryoscolex purkyneilml. for nearly 3 years with a mean generation time of 24 hr.…”
Section: Introductionmentioning
confidence: 99%
“…La plupart des études relatives au métabolisme glucidique des ciliés ont été effectuées jusque-là in vitro (Hungate, 1955 ;Oxford, 1955 ; Howard, 1963 ;Coleman, a et b, 1970Coleman, Davies et Cash, 1972 ;BonhommeFlorentin, 1975 (Hungate, 1942(Hungate, , 1943Coleman, 1960 ;Gutierrez et Davis, 1962 ;Clarke, 1963 ;Mah, 1964 (Thivend, Mercier et Guilbot, 1965 (Jouany, 1978 .…”
unclassified
“…In addition, chloramphenicol was necessary to keep down the growth of associate bacteria and prevent them from overpowering the ciliates. Mah (1963) and Clarke (1963) have also maintained non-axenic cultures for some time, but again the components of the medium have been complex and have included solid materials. Some biochemical studies of organisms from these cultures have been carried out (Mah, 1963 ;Bailey & Clarke, 1963).…”
Section: The Nutrition Of the Rumen Ciliate Protozoamentioning
confidence: 99%